2011
DOI: 10.1038/ajh.2010.194
|View full text |Cite
|
Sign up to set email alerts
|

Home Blood Pressure Monitoring in the Diagnosis and Treatment of Hypertension: A Systematic Review

Abstract: There is conclusive evidence that HBPM is useful for the initial diagnosis and the long-term follow-up of treated hypertension. These data are useful for the optimal application of HBPM, which is widely used in clinical practice. More studies on the cost-effectiveness of HBPM are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
162
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(174 citation statements)
references
References 96 publications
4
162
0
8
Order By: Relevance
“…Comparison of these data with the findings reported in this paper in terms of sensitivity, specificity, predictive and kappa values suggest that HBP is at least as reliable diagnostic method in the setting of RH as it is in the usual population of untreated on treated hypertensives. 9 In the MEDIT --HABP collaborative study of 1441 subjects from Greece, Italy and Spain there was agreement between ABP and HBP in diagnosing sustained hypertension in 86% of the cases, white coat hypertension in 86% and masked hypertension in 89%. 17 By taking ABP as the reference method, the sensitivity, specificity, and positive and negative predictive values of HBP in detecting sustained hypertension were 88%, 85%, and 83% and 90%, respectively, white coat hypertension were 55%, 93%, and 66% and 90%, respectively, and masked hypertension were 57%, 93%, and 50% and 95%, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Comparison of these data with the findings reported in this paper in terms of sensitivity, specificity, predictive and kappa values suggest that HBP is at least as reliable diagnostic method in the setting of RH as it is in the usual population of untreated on treated hypertensives. 9 In the MEDIT --HABP collaborative study of 1441 subjects from Greece, Italy and Spain there was agreement between ABP and HBP in diagnosing sustained hypertension in 86% of the cases, white coat hypertension in 86% and masked hypertension in 89%. 17 By taking ABP as the reference method, the sensitivity, specificity, and positive and negative predictive values of HBP in detecting sustained hypertension were 88%, 85%, and 83% and 90%, respectively, white coat hypertension were 55%, 93%, and 66% and 90%, respectively, and masked hypertension were 57%, 93%, and 50% and 95%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…9 In these studies, the diagnostic ability of HBP was tested in untreated or treated subjects aiming to detect sustained hypertension, and the white coat and masked hypertension phenomena. Comparison of these data with the findings reported in this paper in terms of sensitivity, specificity, predictive and kappa values suggest that HBP is at least as reliable diagnostic method in the setting of RH as it is in the usual population of untreated on treated hypertensives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A recent systematic review found HBPM to be superior to office measurements in diagnosing uncontrolled hypertension, assessing anti-hypertensive drug efficiency, and improving patients' compliance and hypertension control. 5 Moreover, preliminary evidence suggests that HBPM is cost effective. 5 An accurate and validated [6][7][8][9] sphygmomanometer, correct measurement of BP, and adherence to the current specific guidelines regarding when and how BP should be measured at home settings are essentials of reliable HBPM.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, preliminary evidence suggests that HBPM is cost effective. 5 An accurate and validated [6][7][8][9] sphygmomanometer, correct measurement of BP, and adherence to the current specific guidelines regarding when and how BP should be measured at home settings are essentials of reliable HBPM. However, the prevalence of ownership of a home sphygmomanometer and both awareness and compliance of the patients to the HBPM guidelines are less known, especially in developing and underdeveloped countries.…”
Section: Introductionmentioning
confidence: 99%